1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Vertical motion with retarding force

  1. Jan 26, 2008 #1
    Hello everyone, I've used these forums quite a bit and found it very helpful thanks for all you kind souls helping us through the sciences, but today is my first post :P

    I am deriving the velocity of a projectile fired vertically through a retarding force and I continue getting every step the same as the book until the last equation, it may be due to it being nearly 2 in the morning but I wanted to see others thoughts on it to help me learn the reasoning better. (And oh yeah this retarding force is only linear to the velocity)

    so if we have:

    -mg - km[tex]\dot{y}[/tex] = m[tex]\ddot{y}[/tex]

    we can easily work to

    -g - k[tex]\dot{y}[/tex] = [tex]\ddot{y}[/tex]

    [tex]\frac{dv}{dt}[/tex] = -g - kv

    dv = dt(-g - kv)

    [tex]\int\frac{dv}{g + kv}[/tex] = -[tex]\int{dt}[/tex]

    [tex]\frac{1}{k}[/tex] ln(g + kv) = -t + c

    ln(g + kv) = -kt + c

    g + kv = [tex]e^{-kt + c}[/tex]

    This is where the book and I agree to

    but then it arrives to

    v = [tex]\frac{dy}{dt}[/tex] = -[tex]\frac{g}{k}[/tex] + [tex]\frac{kv_0 + g}{k} e^{-kt}[/tex]

    Can someone explain to me how it arrives there? Thank you so much!
  2. jcsd
  3. Jan 26, 2008 #2

    Just notice, you can find c when t = 0, v = v0:

    ln(g + kv) = -kt + c =>
    ln(g + kv0) = -k.0 + c <=>
    c = ln(g + kv0)

    g + kv = [tex]e^{-kt + c}[/tex] <=>
    g + kv = [tex]e^{-kt + ln(g + kv0)}[/tex] <=>
    g + kv = [tex]e^{-kt}[/tex].(g + kv0)
  4. Jan 26, 2008 #3
    ah ok perfect thanks a bunch I kept going around in circles with it last night.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook